Facile synthesis of boric acid-functionalized magnetic covalent organic frameworks and application to magnetic solid-phase extraction of trace endocrine disrupting compounds from meat samples. (15th January 2023) - Liu, Jin; Su, Zhuoqun; Xu, Qinfeng; Shi, Yiheng; Wu, Di; Li, Lin; Wu, Yongning; Li, Guoliang
Graphical abstract: Highlights: A boric acid-functionalized magnetic covalent organic framework nanocomposite (Fe3 O4 @COF@BA) was prepared as adsorbent for the enrichment of EDCs. The satisfactory recoveries were ranged from 88.8 to 104.2 % with low limits of detection in the range of 0.08–0.72 μg kg −1 for EDCs. The presented MSPE-HPLC-MS/MS method pays a new avenue on the extraction and determination of EDCs from other complex matrices. Abstract: A facile approach was proposed for the preparation of boric acid-functionalized core–shell structured magnetic covalent organic framework (COF) nanocomposites through employing the Fe3 O4 nanoparticles as magnetic core, boric acid-functionalized COFs as the shell via sequential post-synthetic modification (denoted as Fe3 O4 @COF@BA). The synthesized nanocomposites showed large specific surface area, high magnetic responsiveness, and desirable chemical and thermal stability. Combined with HPLC-MS/MS, the as-prepared Fe3 O4 @COF@BA composite was applied as a sorbent for magnetic solid-phase extraction (MSPE) of endocrine disrupting compounds (EDCs) from meat samples. Under optimal conditions, the method displays low limits of detection (LODs, 0.08–0.72 μg kg −1 ) and good precision with relative standard deviations (RSD) lower than 5.4 %. The approach was successfully employed for the extraction and detection of EDCs in blank and spiked beef, chicken and pork samples with recovery ranging from 88.8 to 104.2 %.